Synthesis, characterization and evaluation of antidiabetic properties of a new metformin-3- hydroxyflavone complex studied in high fat diet fed - low dose streptozotocin induced experimental type 2 diabetes in wistar rats - C. JAIGANESH; V. ROSHANA DEVI; S. IYYAM PILLAI; S. SUBRAMANIAN (International Journal of Pharma and Bio Sciences, 2017)
Diabetes mellitus is a multifactorial, multisystemic chronic metabolic endocrine disorder arises due to absolute (T1DM) or insufficient secretion of insulin coupled with insulin resistance (T2DM). T2DM accounts for more than 90% of the diabetic population and its incidence is increasing alarmingly worldwide. Among the currently available drugs for the treatment of diabetes such as insulin, thiazolidinediones, gliclazide analogs, α-glucosidase inhibitors, glucagon like peptide-1 receptor agonists and dipeptidyl peptidase-4-inhibitors, metformin occupies a unique importance in its clinical field for the treatment of both T1DM and T2DM due to its safety and efficacy. However, metformin causes lactic acidosis in addition to gastrointestinal tract complications relatively at high doses. Hence, several researchers attempt to synthesize various metformin complexes to minimize the dosage of metformin. The present study is aimed to synthesize a new complex using equimolar concentrations of metformin and 3-hydroxyflavone capable of eliciting maximum antidiabetic properties at a relatively less concentration. Metformin-3-hydroxyflavone complex was synthesized, characterized by IR, Mass, 1H NMR, 13C NMR spectral studies and its safety and efficacy were evaluated in high fat diet fed-low dose STZ induced experimental type 2 diabetes in Wistar rats. The data obtained evidenced that the oral administration of the complex at a concentration of 20mg/kg.b.w./rat/day for 30 days to diabetic rats showed significant antidiabetic and antioxidant properties which was comparable to metformin treatment at a concentration of 50mg/kg.b.w.